#### Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Click to Chat

1800-5470-145

+91 7353221155

CART 0

• 0
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

# solve for x cos^-1(x) + sin^-1(x/2) = pi/6

Sher Mohammad IIT Delhi
askIITians Faculty 174 Points
7 years ago
take sin for both sides,
sin(cos^-1(x) + sin^-1(x/2) )= sin(pi/6)
sin(cos^-1(x))cos(sin^-1(x/2))+sin(sin^-1(x/2) ))cos(cos^-1(x))=.5
sqrt(1-cos(cos^-1(x)))^2)sqrt(1-sin(sin^-1(x/2)))^2)+x^2/2=.5
sqrt(1-x^2)sqrt(1-(x/2)^2)+x^2/2=.5
now , solve for x

b.tech, iit delhi

moon
15 Points
2 years ago

We have cos–1x + sin–1 



2
x
=
6

cos–1x =
6

– sin–1x
 x = cos 


 
2
x
– sin
6
–1
= cos
6

cos 



2
x
sin–1
+ sin
6

sin 



2
x
sin–1
 x =
2
3
cos 2
x
·
2
1
4
x
cos 1–
2
–1  

 

 x =
4
x
4
x
1–
2
3 2

 x –
4
x
=
4
x
1–
2
3 2

4
x
1–
2
3
4
3x 2
  

 

4
x
1–
4
3
16
9x2 2

4
3x2
= 1 –
4
x2

4
x
4
3x2 2
 = 1

4
4x2
= 1
 x2 = 1  x = ±1 But x = 1
Rishi Sharma
askIITians Faculty 646 Points
one year ago
Dear Student,
Please find below the solution to your problem.

Thanks and Regards